Identifying economic hurdles to early adoption of preventative practices: The case of trunk diseases in California winegrape vineyards - Jonathan D. Kaplan; Renaud Travadon; Monica Cooper; Vicken Hillis; Mark Lubell; Kendra Baumgartner (Wine Economics and Policy, 2016)
Despite the high likelihood of infection and substantial yield losses from trunk diseases, many California practitioners wait to adopt field-tested, preventative practices (delayed pruning, double pruning, and application of pruning-wound protectants) until after disease symptoms appear in the vineyard at around 10 years old. We evaluate net benefits from adoption of these practices before symptoms appear in young Cabernet Sauvignon vineyards and after they become apparent in mature vineyards to identify economic hurdles to early adoption. We simulate winegrape production in select counties of California and find widespread benefits from early adoption, increasing vineyard profitable lifespans, in some cases, by close to 50%. However, hurdles may result from uncertainty about the cost and returns from adoption, labor constraints, long time lags in benefits from early adoption, growers' perceived probabilities of infection, and their discount rate. Development of extension resources communicating benefits and potential hurdles to growers likely reduces uncertainty, increasing early adoption. Improvements in efficacy of preventative practices, perhaps by detecting when pathogen spores are released into the vineyard, will increase early adoption. Lastly, practice cost reductions will increase early adoption too, especially when the time it takes for adoption to payoff and infection uncertainty are influential in adoption decisions.
Keywords: 330; Early adoption; Grapevine trunk diseases; Plant-disease management; Preventative practices